Food Safety Assurance Gaps and Microbial Contamination in Beef from the Arosbaya Slaughterhouse: Implications for Public Health Nutrition - Mustofa, Lisa Mufida; Muslihah, Nurul; Rahardjo, Dadik; Kurnijasanti, Rochmah; Helmi Effendi, Mustofa; Rachmawati, Kadek; Mulyoraharjo, Hartanto (Indonesian Journal of Human Nutrition, 2026)
Food safety assurance in slaughterhouses depends on adequate infrastructure, hygienic slaughtering practices, competent personnel, and effective microbiological control. However, studies linking regulatory compliance with microbiological safety remain limited in traditional slaughterhouses in Indonesia. This study evaluated the food safety assurance system and microbiological contamination at the Arosbaya Slaughterhouse, Bangkalan Regency, Indonesia. A mixed-methods evaluative design integrated structured field observations and laboratory analyses to assess infrastructure, Good Slaughtering Practices (GSP), human resource competence, and microbial contamination in meat and the slaughtering environment. Field observations examined compliance with national slaughterhouse regulations, while laboratory testing assessed Total Plate Count (TPC), Salmonella spp., and coliform contamination in 30 beef brisket samples and 9 environmental swab samples from knives, cutting boards, and workers’ hands. The slaughterhouse demonstrated non-compliance with infrastructure standards (41.2%) and human resource requirements (53.3%), while GSP implementation was only partially compliant (66.5%). Although all beef samples were negative for Salmonella spp. and most TPC values remained within acceptable limits, more than 60% of environmental swab samples exceeded national coliform thresholds. This study contributes to food safety assurance by demonstrating that regulatory compliance assessment alone is insufficient to determine meat safety without supporting microbiological validation of carcasses, food-contact surfaces, and workers’ hygiene. The findings provide evidence to strengthen slaughterhouse-based preventive controls, sanitation monitoring, and risk-based food safety evaluation to support safer meat consumption and public health nutrition.